Letter to Georg Bredig from his nephew, November 1908 (1908)
Letter addressed to Georg Bredig (1868-1944) from a relative, presumably his nephew. The writer discusses his studies in Berlin, scientific work, travel plans, and provides an update on his father's health.
Keywords: Bredig, Georg, 1868-1944; Analytical chemistry--Equipment and supplies